INFLUENCE OF CHEMICAL SURFACE MODIFICATION ON MICRO-WEAR CHARACTERISTICS OF SUGARCANE NANOCELLULOSE EPOXY NANOCOMPOSITES - Mohit, H; Selvan, Arul Mozhi (MATTER: International Journal of Science and Technology, 2019)
The waste sugarcane bagasse is the primary agricultural biomass of sugarcane industry and its main constituents is cellulose. These waste sugarcane bagasse can also be applied as reinforcement material in polymer matrix composites. In this present work, the nanocellulose fibers extracted from sugarcane bagasse using salt solution and alkaline treatment process. Sugarcane nanocellulose fiber reinforced epoxy nanocomposites were manufactured by wet layup method. This investigation has been conducted to exhibit the utilization of plant cellulose fiber as the potential reinforcement of synthetic fibers in tribo-composites. The dry sliding wear experiments designed and carried out as per central composite design to determine influence of 3 variable factors such as sliding velocity, sliding distance and load on the wear characteristics of epoxy nanocomposites. From ANOVA (Analysis of variance), it is observed that all three independent parameters plays an important role in the wear characteristics of epoxy nanocomposites, as proven from scanning electron microscope. Simultaneously minimize these tribological characteristics, desirable values of the parameters were depicted to be 5.94 m/s, 5 km and 5 N for sliding velocity, distance and load respectively. From normal probability curves, it is signified that there is a good agreement within the RSM models and experimental results.